The Extent of Awareness and Response of Investors to The Information Content of the Report of The Controller and Its Impact on Investment Decisions (Applied Study) - Muhamad Abdul Aziz Muhamad Saleh Jumaa; Alaa Faleh Al-Khalaf (Journal of Accounting, Business and Management (JABM), 2015)
The audit report issued by the comptroller-references-lists of the annual financial review of the product made of such lists, which show where his mind on the sincerity and fairness of such lists in the expression of the results of the company and its financial position, so is this report is a tool or means of communication? That can be for shareholders and stakeholders in the company to identify the conditions of the company. Is it one of the important mechanisms for the control of the performance-based management company? The importance of the report of the comptroller is in the degree of confidence that it confers on the published financial statements, which are relied upon by users of financial statements in making investment decisions, they have committed to this legislation, the various companies that publish their financial lists to be removing the comptroller's report, as this is important is primary justification in the demand for the service of the audit of financial statements by the users of such lists. In order to achieve the goal of this report, the attention of professional organizations that care for the accounting and auditing profession in all countries of the world and the development of professional standards of ethics and professional conduct, and this concern is continuity in order to pursue the developments and changes in economic life. Despite the efforts to uplift the profession, both at the international level or at the local level, there are many implications that have taken place in the arena of economic life and point the finger of accusation and doubts about the credibility and confidence placed by the comptroller's report on the financial statements, and perhaps months, that the consequences of the collapse has been Many of the corporate giant, despite the report of the comptroller of these companies did not provide an indication or warning signs that, for example, the high rate of companies that went bankrupt at the time, especially in the contemporary United States of America (such as Enron, the energy company, and WorldCom), and the crime committed by the office of Arthur Anderson and his involvement in the cases committed in the manipulation of Enron's energy (Gavious, 2007). These and other events have had the benefit of users of financial statements with respect to the degree of confidence in the report of the comptroller, and reliability in decision-making, studies have tended in the accounting literature in recent times to study and identify the extent of the importance of this report, from the viewpoint of users (will be presented by these studies in a later part of the research), has been developed countries have good chances of these studies, while in developing countries are still studies on this subject is limited and in light of the reviewed studies by the researcher, because of the lack of dissemination of the findings of studies carried out in developed countries to all countries of the world factors variety of the most important environmental factors, the researcher believes that the importance of studying this subject in developing countries because of its importance will to show a researcher at an advanced stage of research. For this arrangement to the above problem, the research is the first two questions: Is available in the report of the controller features and specifications that make it an effective tool of communication, from the perspective of users? And, second: Is the comptroller's report on the annual financial statements in the environment UAE objectivity, confidence and acceptance by the users, to the degree that can be relied upon in making decisions?